An autopsied case of corticobasal degeneration showing severe cerebral atrophy over a protracted disease course of 16 years. Issue 3 (16th December 2014) - Kondo, Daizo; Hino, Hiroaki; Shibuya, Katsuhiko; Fujisawa, Koshiro; Kosaka, Kenji; Hirayasu, Yoshio; Yamamoto, Ryoko; Kasanuki, Koji; Minegishi, Michiko; Sato, Kiyoshi; Hosokawa, Masato; Arai, Tetsuaki; et al.
<x xml:space="preserve">Abstract</x> The patient was a 72‐year‐old Japanese woman. At the age of 57, she started having difficulty performing daily work and developed agraphia. She also exhibited restlessness and loss of interest, and began to speak less. Thereafter, stereotypical behavior, gait disturbance and dysphagia were noted. CT scan demonstrated left‐dominant frontal and temporal lobe atrophy. She died at the age of 72, about 16 years after the onset of symptoms. Neuropathologically, the brain weighed 867 g, and showed remarkable cerebral atrophy with degeneration of the white matter, predominantly in the left dorsal frontal lobe and anterior temporal lobe. Microscopically, severe neuronal loss and gliosis with rarefaction were found in the cerebral cortex, and severe destruction of myelin and axons was observed in the cerebral white matter. Moderate neuronal loss with gliosis was also found in the pallidum and substantia nigra. Gallyas‐Braak staining and tau immunostaining revealed pretangle neurons, NFTs, ballooned neurons and astrocytic plaques in the cerebral cortex, subcortical nuclei and brainstem, and argyrophilic threads and coiled bodies in the subcortical white matter. Tau isoform‐specific immunostaining revealed that most tau‐immunoreactive structures were positive for 4‐repeat (4R) tau, but some of the NFTs were positive for 3‐repeat (3R) tau in the cerebral neocortex. Immunoblotting demonstrated an accumulation of 4R tau in the cerebral cortex and subcortical white matter. The patient was pathologically diagnosed as having corticobasal degeneration. Her long survival course likely accounts for the severe white matter degeneration and accumulation of 3R tau in NFTs.